Uncovering Factors Influencing Millennials’ Use of Non-Standard Words in Twitter - NUR NASHATUL NASUHA, NAZMAN; Su hie, Ting; Kee Man, Chuah (Universiti Kebangsaan Malaysia, 2022)
Social media communication has its own language features and one aspect is modified spelling of standard words. Social media users use shortened words with full awareness of the meanings, and new non-standard words are constantly added to the repertoire of social media language. A pertinent question is whether social media users learn these non-standard words to use or whether they also contribute to the vocabulary used in social media communication. The study examined Malaysian millennials’ use of non-standard words in Twitter and their reasons for shortening words. For the nonstandard words, data were collected from 200 active Twitter users whereas data on reasons for shortening words were collected from 30 users. The results showed that the Malaysian millennials frequently used non-standard spelling of words. The three top words were “ni” (this), “nak” (want), and X (negation). The main reasons for the Twitter users to shorten words were the 280-character limit per tweet, user convenience, and characteristics of words. The Twitter users felt free to create new spellings of standard words at times for fun, but most of the time, they use the common nonstandard words. The Malaysian millennials reported that they were inclined to shorten long and complex words, and words with many vowels. The study suggests that Twitter users balance between speed in communication and preservation of meaning when using non-standard words.